Perkembangan Digitalisasi Terhadap Sektor Keuangan Pada Usaha UMKM Bubur Cianjur di Masa Pandemi Covid-19 - Sarah Elvina Aulia; Astin Dewi Chofifah; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The role of MSMEs in the Indonesian economy is very important and strategic, during the Covid-19 pandemic as we experienced it greatly affected all sectors of people's lives. Many MSMEs have experienced a drastic decline in production due to Covid-19 and threaten the national economy. In order for the business to continue to run smoothly, business actors have shifted to keep up with technological developments, not only in sales but in the online financial sector. With the presence of fintech, MSME owners get hope during the Covid-19 pandemic to run their business. The research used a descriptive method with an observative approach, aiming to find out the development of digitization in the Cianjur Chicken Porridge financial sector. The results of this study are that business actors apply digitalization development in their financial sector, this helps to reduce physical contact and reduce the spread of the Covid-19 virus. Payments made in non-cash via Qris and Shopee-pay. Efforts to make this development run smoothly can be done by implementing innovations and services in Digitalization enabling the financial sector to develop new products and services that are more efficient and easy to use, besides that Through partnerships and secure data exchange, the financial sector can face challenges and better digital opportunities, and build a sustainable and innovative ecosystem.